TOWARDS A CIRCULAR ECONOMY IN ROMANIA - Tiberiu Cristian AVRĂMESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2021)
The transition towards a circular economy, in which the value of products, materials and resources is remains in the economy for as long as possible and the production of waste is reduced to a minimum, has gained special attention lately on the agenda of public authorities, business environment, research institutes and non-governmental organizations. The paper aims to identify ways to implement the circular economy in Romania, the stakeholders, as well as ways to promote the circular economy applicable to the Romanian development model. The paper brings to the fore the efficient use of resources as a cross-cutting principle of the circular economy, which can be applicable to any sector of activity. From this perspective, the recirculation of resources is the key to achieving the circular economy, respectively the transition to the green economy in Romania.